Malignant melanoma of the oral cavity: Report of two cases - Anita Munde; Monica Vivek Juvekar; Ravindra R. Karle; Pranali Wankhede (Wolters Kluwer Medknow Publications, 2014)
Primary malignant melanoma is a rare and aggressive neoplasm that originates from the proliferation of melanocytes. Although, it comprises 1.3% of all cancers, malignant melanoma of the oral cavity accounts for only 0.2-8% of all reported melanomas and occurs approximately 4 times more frequently in the oral mucosa of the upper jaw, usually on the palate or alveolar gingivae. Most of the mucosal melanomas are usually asymptomatic in early stages, and presents as pigmented patch or a mass delaying the diagnosis until symptoms of swelling, ulceration, bleeding, or loosening of teeth are noted. The prognosis is extremely poor, especially in advanced stages. Therefore, any pigmented lesion of undetermined origin should always be biopsied. We herewith report of two cases of oral malignant melanoma in a 60 and 75-year-old female.